Genetic improvement and conservation of native forest resources in Chile - Gutiérrez, B. (Forest Systems, 2003)
In Chile, the native forest resources have been historically exposed to degradation processes that have decreased their genetic variability and reduced their productive potential. Despite that, these forests represent a great opportunity to contribute to the needed diversif ication of the local forestry sector, which at the moment is based on the industrial use of moterrey pine (Pinus radiata) and eucalypts plantations, mainly E. globulus. To correct this situation, in the last years intense programs of genetic tree improvement have been implemented by the Chilean Forestry Institute (INFOR), to restore the genetic variability and to improve the productive capacity of the main species of these forests. Such programs take into account the conservational and productive features of the resource. In this article, the main causes of degradation of the Chilean natural forests and the most remarkable topics of the conservation and genetic improvement projects that the Chilean Forestry Institute (INFOR) executed for the species Nothofagus alpina, N. obliqua, N. pumilio, N. dombeyi and Laureliopsis sempervirens are discussed.